Wild eyes - Silver, Elsie (Silver, Elsie. Rose Hill series, 2024)
"A rugged mountain town seemed like the perfect escape from a life in shambles. But on day one, she ran full tilt into the world's hottest single dad, and now all her plans are ruined. As a chart-topping country singer with a recent streak of bad press, it's hard for Skylar Stone to find any peace. But she finds it in Rose Hill. With a little boy and a little girl who steal her heart just as thoroughly as their dad. Weston Belmont. The man is a shameless flirt. He oozes confidence and masculinity in a way that's downright distracting. And in bed? He's addictive. Everything with him is wild and impulsive, and Skylar is desperate to regain some control. But no one has supported her like West does. And no one has ever made her feel as loved as he does either. So, while Skylar's brain says settling down with a small-town horse trainer is impossible...her heart says she's right where she belongs. Still, her life as a celebrity haunts her. It has the power to pull she and West apart. She can see in his eyes that he wants her to stay. And she wants that too. But she knows better than anyone that you don't always get what you want"--